2019
DOI: 10.3390/jcm8071024
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Chronic Obstructive Pulmonary Disease (COPD) Impair Survival in Lung Cancer Patients Receiving Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitor (EGFR-TKI): A Nationwide, Population-Based Cohort Study

Abstract: The emergence of epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) caused a paradigm shift in the treatment of non-small cell lung cancer (NSCLC). Although several clinicopathologic factors to predict the response to and survival on EGFR-TKI were recognized, its efficacy has not been confirmed for patients with underlying pulmonary disease, such as chronic obstructive pulmonary disease (COPD). We conducted the study to evaluate the impact of COPD on survival for NSCLC patients that underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This result is consistent with the results of the prior large-scale clinical study. 10 However, that study did not describe more genetic information. Previous literatures have reported that TP53 is an unfavorable factor for the prognosis and targeted therapy of lung cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This result is consistent with the results of the prior large-scale clinical study. 10 However, that study did not describe more genetic information. Previous literatures have reported that TP53 is an unfavorable factor for the prognosis and targeted therapy of lung cancer.…”
Section: Discussionmentioning
confidence: 94%
“…A retrospective study based on the National Health Insurance Research Database in Taiwan indicated lung cancer patients with EGFR-TKI treatment had a worse survival outcome if patients had pre-existing COPD. 10 However, the patients in this study lacked further description of genetic mutations. Another retrospective immunotherapy research investigated the clinical impact of COPD on the treatment response to palliative pembrolizumab in non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 92%